2023
DOI: 10.1029/2022ea002733
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Regional Atmospheric Model Simulations Coupled and Uncoupled to a Regional Ocean Model of the Indian Summer Monsoon

Abstract: The Indian summer monsoon (ISM) is an important tropical coupled ocean-atmosphere system. The intraseasonal oscillations (ISOs), are one of the dominant features of the ISM (Krishnamurthy & Shukla, 2007;Sikka & Gadgil, 1980). Many studies suggest that coupled ocean-atmosphere climate models are the best tools to simulate the ISM and its variability, realistically (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Both the URSM and CRSM have been forced at the lateral boundaries with integrations of the Community Climate System Model version 4 (CCSM4; Gent et al, 2011), which was part of the Coupled Model Intercomparison Project version 5 (CMIP5; Taylor et al, 2012). It has been shown that the CCSM4 model that participated in CMIP5 was one of the five top-ranked models in simulating the present-day global climate (Sheffield et al, 2013) and is widely used for dynamical downscaling over various regions Jayasankar et al, 2023). The atmospheric component of the RCM is forced at 6-h intervals while the oceanic component of the RCM is forced at monthly intervals with the boundary conditions provided by the corresponding components of CCSM4.…”
Section: Model Detailsmentioning
confidence: 99%
“…Both the URSM and CRSM have been forced at the lateral boundaries with integrations of the Community Climate System Model version 4 (CCSM4; Gent et al, 2011), which was part of the Coupled Model Intercomparison Project version 5 (CMIP5; Taylor et al, 2012). It has been shown that the CCSM4 model that participated in CMIP5 was one of the five top-ranked models in simulating the present-day global climate (Sheffield et al, 2013) and is widely used for dynamical downscaling over various regions Jayasankar et al, 2023). The atmospheric component of the RCM is forced at 6-h intervals while the oceanic component of the RCM is forced at monthly intervals with the boundary conditions provided by the corresponding components of CCSM4.…”
Section: Model Detailsmentioning
confidence: 99%